A gastronomia como meio condutor de desenvolvimento do turismo na antiga zona primitiva de colonização italiana (RS) - Colonetti, Charlie Tecchio (My University, 2018)
The gastronomy has helped in the construction of the tourist activity, with diversified services and elaboration of new Routes. One can even associate in the development of certain Regions. The research identifies the gastronomy present in the Serra Gaúcha specifically in de Region of Grape and Wine with a focus on the hybridization of Italian cuisine in its restaurants with tourist appeal (which portrays the Italian memory) in consolidated tourism Routes. The methodology of this research is characterized by being exploratory and descriptive. It is done by technical procedures as a case study; Regarding the research question, it is considered a qualitativequantitative study; the data collection was done through a questionnaire and bibliographic research; aiming to understand the process of hybridization and the positioning of its gastronomic offer regarding this issue and the data processed for use by an analysis with reference in the comprehensive method is adopted in the treatment. Several different denominations have been found that discredit the gastronomy of the Serra Gaúcha. Therefore, the Immigration Kitchen is the proposal of the researcher, as being the one that would fit best in different denominations. The Immigration Kitchen can make Serra Gaúcha invoke a destination also known for gastronomic tourism, where it values its ancestors and conveys the pride and strength of it through food
A gastronomia tem auxiliado na construção da atividade turística, com serviços diversificados e elaboração de novos roteiros. Pode-se inclusive associá-la ao desenvolvimento de determinadas regiões. A pesquisa identifica a gastronomia presente na Serra Gaúcha especificamente na Região Uva e Vinho, com enfoque para a hibridização da culinária italiana, nos seus restaurantes com apelo turístico (que retrate a memória italiana) em roteiros turísticos consolidados. A metodologia desta pesquisa caracteriza-se por ser exploratória e descritiva. Faz-se por procedimentos técnicos como estudo de caso; quanto à questão de pesquisa,considera-se um estudo quali-quantitativo; a coleta de dados foi realizada através de questionário e de pesquisa bibliográfica, objetivando compreender o processo de hibridização e o posicionamento de sua oferta gastronômica quanto a esta questão e adota-se, no tratamento dos dados trabalhados, a utilização por uma análise com referência no método compreensivo. Foram encontradas diversas denominações diferentes, que desvirtuam a gastronomia da Serra gaúcha. Logo, a Cozinha de Imigração é proposta pelo autor da pesquisa, como sendo a que melhor se encaixaria em diversas denominações. A Cozinha de Imigração pode fazer com que a Serra gaúcha invoque um destino também conhecido pelo turismo gastronômico, em que valoriza seus antepassados e transmite o seu orgulho e a força, através da alimentação.
Keywords: Turismo cultural; Gastronomia; Fusão cultural; Heritage tourism; Gastronomy; Cultural fusion